Low-Level Laser Therapy, Photobiomodulation, and Photodynamics with Photosensitizer Combination in Dentistry: A Systematic Review: LLLT, PBM and PDT in Dentistry - Muntadir, Lila; Narmada, Ida Bagus; Sulisetyawati, Theresia Indah Budhy; Setiawatie, Ernie Maduratna; Apsari, Retna; Triwardhani, Ari; Nugraha, Alexander Patera (Journal of Lasers in Medical Sciences, 2026)
Introduction: Photobiomodulation (PBM), photodynamic therapy (PDT), and combined therapies have recently attracted attention due to their potentially beneficial antimicrobial, analgesic, and regenerative properties in dentistry. Although PBM and PDT have been extensively studied separately, evidence regarding their combined application is limited. This study aimed to systematically review studies employing combined PBM + PDT protocols in dental and oral applications. Methods: A systematic search of PubMed, ScienceDirect, ProQuest, DOAJ, and Google Scholar (2021–2025) identified original studies using combined PBM and PDT. Inclusion criteria: dentalrelated PBM + PDT, clear dosimetric parameters, English, primary research. Exclusion: PBMonly, PDT-only, non-dental studies, insufficient parameters Inclusion criteria: dental-related PBM and PDT; clearly reported dosimetric parameters; English language; primary research. Results: Eight studies met eligibility criteria. Applications included oral mucositis management, orthodontic acceleration, endodontic disinfection, oral lesion therapy, antimicrobial modulation, and regenerative endodontics. Combined PBM + PDT demonstrated enhanced antimicrobial activity, reduced inflammatory markers, accelerated wound healing, and improved patientreported outcomes compared with single-modality treatments. Conclusion: PBM + PDT shows synergistic therapeutic potential across multiple dental fields. Despite promising outcomes, heterogeneity in parameters remains a limitation. Standardized protocols and high-quality clinical trials are required.